Proyecto de factibilidad para la implementación de una empresa productora y comercializadora de snack de fruta deshidratada en la ciudad de Loja - Vacacela Ramón, Rocio del Pilar (2015)
This Thesis Commercial Engineering's main objective is to perform a feasibility project to implement an enterprise engaged in the production and marketing of Dried Fruit Snack in the city of Loja, so this project will help determine whether the project is feasible or not. For the implementation of this project in the first place the specific objectives that will help them to perform each of the relevant studies were raised, the demand is also determined by the city of Loja, and in this way start with market research and determine effective demand and supply in the city of Loja, also within the technical study utilized capacity requiring the company is determined, the legal and administrative organization of the company are set, and through financial study to determine the feasibility achieved of this project. The methodology is based on conventional methods such as historical, inductive and deductive method that will allow them to obtain all the information required by the project helping to techniques such as surveys, interviews and literature review, giving them the necessary guidelines for both consumer and competition. For the development of the research was necessary to obtain a sample population that using the last census of 2010 the number of surveys that should be applied in the city of Loja was obtained being 321 quantity, and in this way to obtain specific data on the tastes and preferences of consumers. Market Research for Business "FRUTICKS" CIA. LTDA. is aimed at the urban population of the city of Loja who wish to improve their quality of life by consuming 100% natural and preservative threatening their health. With this background it is determined that the actual demand for this product is 35139 families. The company "FRUTICKS"'s vision is ranked among the best companies in the city of Loja, always walking hand in hand with the changing attitudes of 6 consumers and trying to satisfy all your needs as to meet all the goals that the company proposed will meet the production quantity established, to thereby accomplish the estimated gains in the project and the company to become the number one city. The company will be located in the city of Loja in the urbanization The Paradise in the Canaries Hummingbirds and streets, this place has been considered due to good accessibility and because it meets all the requirements for the company to function properly. The Company "Fruticks" features satisfy the tastes and needs of consumers is why the surveys by the lojanas families decide to make dried fruit Snack Strawberry, and will start with 80% of the capacity installed which means that the first year is to work with 91520 pounds. The breakdown of the fixed assets of $ 35,785 is detailed, the deferred asset is $ 2,724 and current assets is $ 7945,41, for a total of $ 46454, the legal structure of the company will Accountability limited, formed by two partners bring to the company a total of $ 13936 U.S. dollars by credit and the National Development Bank in the amount of $32518. The profit and loss account shows a net profit of $ 14365,11 in the first year and will increase for subsequent years. The project evaluation found that Neto (VAN) Present Value is positive with a value of $ 32238; Internal Rate of Return (IRR) is 37,8%, the cost / benefit ratio (CBR) indicates that for every dollar the company will get 0.21 cents; Period Recovery Capital (PRC) is achieved in 3 years; and based on Sensitivity Analysis (SA) a very satisfactory result which allows a decrease in revenue by 14,50% and increased costs of 17,68% is demonstrated. With all the above has shown that the project in question is feasible and therefore is recommended to implement the company in the city of Loja.